Sustainability of a Given Ten-Week Motor Skills Training Program for Children with Developmental Coordination Disorder - Orifjon Saidmamatov; Ko'palov Sanjarbek; Olga Vasconcelos; Paula Rodrigues (MDPI AG, 2022)
The aim of this research was to determine the sustainability of a given ten-week motor skills training program for children with developmental coordination disorder (DCD). Children with DCD in four kindergartens in the Khorezm region of Uzbekistan were selected to take part in the study. Participants were 24 children between 4 and 6 years old (5.25 ± 0.13 years), assigned to an intervention group (IG: 17 children; 10 boys) and a control group (CG: 7 children; 4 boys). The Movement Assessment Battery for Children (MABC-2) was used to assess motor competence pre-intervention, post-intervention, and retention test measurement after 18 months. The retention test results for the IG indicated a decline in all three motor domains of MABC-2. Despite this, the results that were acquired during the retention test came out to be better than the results that were achieved during the pre-test. At the same time, children who were allocated to the CG maintained their performance. The findings suggest that a preschool-based motor skill training program has the potential to increase motor skills in children with DCD. However, the positive benefits produced by the intervention may decrease over the course of time if the intervention is not continued.